2022
DOI: 10.1038/s41598-022-24129-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of macular structure, function, and vessel density with foveal threshold in advanced glaucoma

Abstract: Identifying new biomarkers associated with central visual function impairment is important in advanced glaucoma patients. This retrospective cross-sectional study enrolled 154 eyes from 154 subjects, consisting of 86 patients with advanced open-angle glaucoma (mean deviation of 24-2 visual field [VF] tests < − 15 dB) and 68 healthy controls. Structure, function, and vessel density (VD) parameters were obtained using optical coherence tomography (OCT), 24-2 standard automated perimetry, and OCT angiography, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 50 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Although the role of the choroid in the pathogenesis of glaucoma remains unclear, we suggest that a thin subfoveal choroid may be associated with decreased blood flow in the fovea region, which can lead to photoreceptor dysfunction that subsequently affects the functional status of the overlying outer retina. Recently, associations between macular microvasculature and central visual function or BCVA have been reported by several studies using OCT angiography [12][13][14], which found that macular microvascular density, especially from the deep layer, was an important independent predictor of BCVA [12][13][14]. Additionally, Song et al [14] demonstrated that the severity of central VF impairment can vary significantly according to the status of deep macular microvasculature, despite similar VF MD and macular structural damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the role of the choroid in the pathogenesis of glaucoma remains unclear, we suggest that a thin subfoveal choroid may be associated with decreased blood flow in the fovea region, which can lead to photoreceptor dysfunction that subsequently affects the functional status of the overlying outer retina. Recently, associations between macular microvasculature and central visual function or BCVA have been reported by several studies using OCT angiography [12][13][14], which found that macular microvascular density, especially from the deep layer, was an important independent predictor of BCVA [12][13][14]. Additionally, Song et al [14] demonstrated that the severity of central VF impairment can vary significantly according to the status of deep macular microvasculature, despite similar VF MD and macular structural damage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, associations between macular microvasculature and central visual function or BCVA have been reported by several studies using OCT angiography [12][13][14], which found that macular microvascular density, especially from the deep layer, was an important independent predictor of BCVA [12][13][14]. Additionally, Song et al [14] demonstrated that the severity of central VF impairment can vary significantly according to the status of deep macular microvasculature, despite similar VF MD and macular structural damage. Since the parafoveal region can support central visual function, impairment of the blood flow at the parafoveal retina can affect central visual function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 19 In addition, since there are no universally accepted criteria for the classification of advanced glaucoma, an MD ≤ −15 dB criterion was selected for this study based on previously published studies. 9 , 20 , 21 …”
Section: Methodsmentioning
confidence: 99%
“… 4 , 5 Several prior studies, including our own reports, have demonstrated the presence of significant correlations between the reduction in OCT/OCTA parameters and the loss of VF sensitivity (VFS) in glaucoma based on a cross-sectional study design. 6 9 …”
mentioning
confidence: 99%